2019
DOI: 10.1007/s40789-019-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the chemical leaching (inorgano-leaching), bio-leaching and desulphurisation of coals

Abstract: Coal still remains an important source of power generation world over. Along with its usage, comes unwanted generation of noxious gas emissions, toxic metal releases into wastewater and other pollutants which ultimately lead to environmental concerns. So cleaning of coal through physical or chemical processes becomes utmost important. There are several coals which cannot be cleaned by physical beneficiation techniques to produce low ash cleaner coals. Such coals can be cleaned only through chemical cleaning te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 86 publications
2
14
0
6
Order By: Relevance
“…It can also be observed that the percent removal of Sulfur was on higher side for the particle size of 10 Mesh as compared to 6 Mesh with both of the solvents. Similar trends were observed in previous work conducted by [14], [17].…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…It can also be observed that the percent removal of Sulfur was on higher side for the particle size of 10 Mesh as compared to 6 Mesh with both of the solvents. Similar trends were observed in previous work conducted by [14], [17].…”
Section: Methodssupporting
confidence: 91%
“…Three different concentrations (wt. %) of each solvent were prepared using standard dilution method [17]. Solutions were prepared by dissolving 5 gm, 15 gm, and 30 gm of NaOH and HNO3 in 100 milliliter of distilled water and mixed thoroughly.…”
Section: Preparation Of Different Concentration Of Hno3/naoh Solutionsmentioning
confidence: 99%
“…The energy consumption assessment was based on experiences and on data from sludge drying plants [8], HTC, and slow pyrolysis [4,5,9]. The energy consumption comparison between drying and HTC plants was calculated considering a sludge input of 5000kg, at 20% dry matter.…”
Section: Mass Balance and Energy Consumptionmentioning
confidence: 99%
“…Sometimes, mild acid washing also reduced the extra sodium compounds along with acid-soluble minerals in coal. 11 Previous reports on coal treatment also indicated that the types of leaching reagents affected the properties of coal or carbon materials. For instance, Starck et al 12 reported that the coal treatment with HCl and HF acid solution could remove ash and signicantly modify the surface chemistry of lignite, which was able to develop the adsorbent properties of lignite.…”
Section: Introductionmentioning
confidence: 99%